UNESCO biosphere reserves show demand for multifunctional agriculture. (15th October 2022) - König, Hannes Jochen; Uthes, Sandra; Ostermann-Miyashita, Emu-Felicitas; Eufemia, Luca; Hemminger, Karoline; Hermanns, Till; Bethwell, Claudia; Stachow, Ulrich; Helming, Katharina
Abstract: Sustainable landscape management of protected areas in UNESCO-biosphere reserves (BR) has become an increasingly important topic for academics and environmental practitioners, yet it remains unclear how this can be operationalized in actual regional circumstances. To achieve positive and measurable sustainability impacts, effective BR management on the ground requires supplementary methods to conceive the unique territorial, political, economic and social characteristics of each case while also considering the needs and visions of different stakeholder groups. In this study, we used the Framework for Participatory Impact Assessment (FoPIA) to assess future projections of current land management strategies and possible alternatives in five BR in Germany. The FoPIA method helped identify major differences in the regional BR contexts, including defining the sustainability problem and sustainability challenges. It also proved suitable for fostering stakeholder dialog with regard to current and future sustainable land use management, particularly for the BR transition zones. Our results predict multiple negative impacts resulting from of a continuation of current practices, which are compared against the assessed outcomes of alternative multifunctional pathways. We use these findings to discuss recommendations and challenges for sustainable management of biosphere reserves, the potential of implementing the FoPIA in BR, and perspectives for further research needs. Highlights: A participatory scenario development and assessment study for five UNESCO-biosphere reserves in Germany is presented. The presented approach can contribute to improving the required stakeholder participation in biosphere reserves. Developed scenarios ranged between a focus on singular environmental objectives and multifunctional land use scenarios. Scenario results showed negative environmental and socioeconomic impacts of ongoing trend scenarios. Multifunctional land use scenarios were assessed to have a higher future sustainability potential.